Usage Impact Smartphone Against Students and BK Teacher's Efforts in Overcoming It - Salsabila, Fitri; Masril, Masril; Asmita, Wenda; Zubaidah, Zubaidah; Denis, Sourbron (Yayasan Minang Darussalam, 2023)
From research conducted in the field, it was found that Smartphones can boost up which provides new insights about subject matter so that it supports the value of assignments and encourages me to achieve academic achievement. Smartphones in social life can strengthen friendly relations with friends who are far away, can get information from friends about the latest things, get lesson information from friends at other schools. The negative effects of smartphones on learning can interfere with managing study time, inconsistent doing assignments and easily diverting from doing assignments. There are adult advertisements that interfere with finding assignment references or when doing assignments so that they have an impact on students' understanding of pornographic matters. The counseling teacher's efforts to use smartphones for academic achievement from the results of the research conducted provide an illustration that the counseling teacher's business is to provide tutoring services, career guidance, counseling services by trying to use smartphones as a supporting medium in carrying out counseling so that the expected results can encourage achievement. student academic. The counseling teacher's effort to counteract the negative influence of Smartphones on learning is to apply a prevention function before learning is disrupted. Students' understanding of the use of Smartphones helps in broadening knowledge that is not found in schools so that they can find out what learning they want to find out.